AWAKENING OF RIGHT-WING IN EUROPEAN UNION – THE WAY TO THE NEW EUROPE OR “FALSE ALARM“? - Petrović, Rajko Č (Politeia, 2018)
The European Union today faces difficult challenges. Numerous political, economic, social, cultural and identity issues in the European Union have not been treated satisfactorily, causing direct consequences in its political life. More and more citizens are unhappy with the way in which the current political elite of the European Union responds to these challenges, while the opposition political parties (whether left-wing or right-wing center parties) do not offer a significantly different alternative. For these reasons, over the past two decades, the European Union has gradually revived the political right-wing. Whether it's a new right-wing center, far right-wing or an extreme right-wing - a new wave of the right-wing gives citizens of the Union an authentic alternative policy. It is about parties that are ready to deal with the problems of migration, culture, religion, identity, as well as the integration of minorities into the European model of life. Although still media-satanized and labeled as a fascist or Nazi, the European right-wing year after year is stronger - from Hungary, through Slovakia, Poland, Germany and Austria, all the way to the Netherlands and Great Britain. The ruling political elite in Brussels called the wave of the rise of the right-wing in the Union a "false alarm", while the relevant data from the previous election cycles of the same, as well as public opinion polls show a completely opposite tendency - the desire of a large part of the citizens to create "New Europe". The future of the European Union has become one of the most important themes, both on the political scene of the member states of the European Union, as well as in the candidate countries, but also in the rest of the world. The European Union as a whole is confronted with problems of political, economic, social, cultural and even religious nature. History has taught us that in almost every society in crisis times the political party of the center is weak and losing its significance, and political power moves towards the poles of the political spectrum to the left or right pole. Right-wing  political parties in the European Union now use the crisis in the best way.